A GSM-Based Fault Detection on Overhead Distribution Lines - Charles Ofori; Joseph Cudjoe Attachie; Felix Obeng-Adjapong (JURNAL NASIONAL TEKNIK ELEKTRO, 2023)
Power distribution in Ghana is managed by the Electricity Company of Ghana (ECG) which is responsible for ensuring accessibility of electricity to consumers. One of the challenges that affect the effective operation of ECG is the slow response to faults on the overhead distribution lines. Fault detection on the distribution lines is a very tedious activity but a necessary procedure to ensure efficient power distribution to consumers. This paper seeks to design a system that can detect faults, the type of faults and their location before they cause any casualties to transformers and other power system equipment. This would replace the primitive method of patrolling and manual inspection of faults currently done by the Electricity Company of Ghana (ECG). This objective was achieved using a GSM-based system on an Arduino platform and ATmega 328P microcontroller to locate the occurrence of faults efficiently. Faults are introduced into the system by triggering the type of fault on the Arduino platform which opens the corresponding relay of the line fault. The opening of this relay sends a signal to the microcontroller and a corresponding LED which switches to display the type of fault. The microcontroller then communicates to the GSM module which displays the said fault and location on a display screen with the help of a virtual terminal. This system was tested under the various unsymmetrical faults to show the efficiency of the system using C++ programming. The simulation shows that the system offers a fast fault response time.